Prevalence of obstructive sleep apnea risk in patients with type 2 diabetes mellitus in an urban field practice area of a Government Medical College, Nagpur: a cross-sectional study - Sanjay, Aade Vicky; Bhelkar, Sandeep; Narlawar, Uday; Padyal, Pratik (International Journal Of Community Medicine And Public Health, 2026)
Background: Obstructive sleep apnea (OSA) is a common but frequently undiagnosed sleep disorder characterized by recurrent upper airway obstruction during sleep. Patients with type 2 diabetes mellitus (T2DM) are at increased risk of OSA because of shared risk factors such as obesity and metabolic abnormalities. This study assessed the prevalence of OSA risk among patients with T2DM using a validated screening tool. Methods: A cross-sectional study was conducted among 110 patients with T2DM attending the urban health training centre of Government Medical College, Nagpur. OSA risk was assessed using the STOP-Bang questionnaire. Demographic and clinical data, including body mass index (BMI) and comorbidities, were collected. Participants were categorized as having low, intermediate, or high risk of OSA based on STOP-Bang scores. Descriptive statistics and univariate analysis were used for data analysis. Results: Of the 110 participants, 59.1% were male and 60.9% were aged ≥60 years. Based on STOP-Bang scores, 29% were at low risk, 36% at intermediate risk, and 35% at high risk of OSA. High OSA risk was significantly associated with age ≥60 years (p<0.001) and hypertension (p<0.0001). Conclusions: More than one-third of patients with T2DM were at high risk of OSA. Increasing age and hypertension were significantly associated with higher OSA risk. Routine OSA screening among patients with T2DM may facilitate early identification and timely management of this potentially underdiagnosed condition.